Environmental sustainability in the dental curriculum: a scoping review - Omar Bamedhaf; Hira Salman; Shakeel Ahmed Tegginmani; Shaista Salman Guraya (BMC Medical Education)
Abstract Background Environmental sustainability (ES) is an essential consideration in modern healthcare, including dentistry, due to the industry's significant ecological footprint. The dental sector generates considerable waste, consumes high levels of energy and water, and contributes to pollution through materials such as dental amalgam. In response, integrating ES principles into dental curricula has emerged as a vital strategy to foster environmentally responsible practitioners. Despite various initiatives and frameworks, including the United Nations Sustainable Development Goals (SDGs), the extent and effectiveness of ES education in dental programs remain inconsistent. This scoping review aims to map the global landscape of ES integration within dental education, identifying existing practices, barriers, and opportunities for improvement. Methods This scoping review followed Arksey and O'Malley’s framework to systematically identify and analyze studies on ES in dental curricula. A structured literature search was conducted across PubMed, SCOPUS, and Embase using predefined MeSH terms and keywords related to dental education and sustainability. Studies published within the last ten years were included, with a final selection of 23 studies meeting the inclusion criteria. The extracted data were analyzed using Braun and Clarke’s thematic analysis framework, ensuring a structured and systematic categorization of emerging themes. The thematic analysis involved familiarization with the data, generation of initial codes, searching for themes, reviewing themes for coherence, defining and naming them, and finally reporting the results. Results The review identified six major themes using a deductive approach, guided by David Cook’s educational research framework, to categorize findings into three key levels: (1) Descriptive studies, which assessed awareness and knowledge levels among students and faculty; (2) Justification studies, which evaluated the effectiveness of ES focused educational interventions; and (3) Clarification studies, which explored systemic barriers, best practices, and policy-level implications. Through this structured classification, the themes that emerged included (1) awareness and perceptions of ES, (2) barriers to implementation, (3) gaps in ES education, (4) best practices for integrating ES, (5) trends and future directions, and (6) the effectiveness of educational interventions. While structured training programs demonstrated positive impacts on student engagement and knowledge, ES education in dental curricula remains inconsistent, lacking standardized learning objectives, institutional policies, and faculty training. Conclusion This review underscores the urgent need for a structured and comprehensive integration of ES within dental education. While ES awareness is increasing, significant gaps remain in faculty preparedness, curriculum standardization, and institutional support. Addressing these challenges requires coordinated efforts, including policy mandates, faculty development programs, and innovative teaching strategies. By embedding ES into dental curricula, institutions can equip future dental professionals with the necessary knowledge and skills to implement environmentally responsible practices and contribute to a more sustainable healthcare system.